Numerical study of braced excavation performance in stiff clay - Choong, Chee Kong (2017)
Braced excavation is increasingly adopted to construct deep underground structures in built-up metropolitan areas due to prevalent land constraint nowadays. The performance of a braced excavation is predominantly concerned with the overall system stability and the wall deformation. Therefore, the braced excavation system should be designed such that there is no instability and the deformation does not exceed the acceptable level. In this project, the main objective is to analyze the effects of varying several parameters on the braced excavation performance in stiff clay deposit by using commercial finite element program, PLAXIS 2D. The parameters include vertical strut spacing, wall stiffness as well as excavation width. Besides that, a special case in which the final strut is omitted is also considered. An advanced soil model, namely Hardening Soil model is adopted to simulate more realistically the non-linear stress-strain behavior of the soil. The performance of the braced excavation is evaluated in terms of the maximum wall lateral deflection, maximum wall bending moment, strut forces as well as the basal heave factor of safety. The Peck’s Apparent Pressure Diagram (APD) is also plotted and compared to the computed strut pressure as well. In total, 45 cases were considered in this project. The analyses indicated that the braced excavation performance is influenced considerably by the variation of the mentioned parameters. Increasing the vertical strut spacing adversely affected the performance of the excavation using sheet pile wall as compared to diaphragm walls. The diaphragm wall with the highest bending stiffness showed the largest deflection occurred at toe and exhibited the highest bending moment when the wall stiffness increased. Furthermore, the numerical results also revealed that the wider the excavation, the more significantly the wall bending moment as well as the maximum wall deflection increased. In addition, the effect of omitting the last strut led to the most significant increase of maximum lateral deflection of sheet pile wall and had much lesser impact on the performance of the diaphragm walls. Apart from that, the analytical results indicated that the basal heave stability was not significantly affected by varying the studied parameters. Lastly, this project also concluded that the Peck’s empirical APD significantly underestimated the force in the lower struts.